Income Mobility in New Zealand: A Descriptive Analysis - Kristie Carter; Penny Mok; Trinh Le (New Zealand Government, The Treasury, 2014)
The purpose of this paper is to examine the absolute and relative income mobility in disposable income in New Zealand using the full longitudinal data from the Survey of Family, Income and Employment (SoFIE) from 2002 to 2010. To summarise the patterns of mobility, we analyse the income changes over the short-term (annual) and a longer term interval (eight years). There is change in incomes between one year and the next, with over 60 percent of the population changing income decile group. The movements in income group are more of a short distance (to adjacent income groups) than long distance. There is substantial change in income over the long-run in both absolute and relative income. Only 22 percent stay in the same income decile group eight years later. The findings of mobility income are similar to those found in other international longitudinal surveys.
Keywords: D31; D63; 330; Income; Mobility; Longitudinal data; Einkommensverteilung; Soziale Mobilität; Privater Haushalt; Haushaltseinkommen; Neuseeland